TYPES OF CODE SWITCHING IN MELANEY RICARDOâ€™S YOUTUBE CHANNEL - Ni Made Nopiasih; I Gusti Bagus Wahyu Nugraha Putra (Universitas Warmadewa, 2023)
This study aims to identify the various types of code-switching used by Melaney Ricardo and Zacklee on the YouTube channel Melaney Ricardo. The data in this study were represented using a descriptive qualitative method based on Romaineâ€™s code-switching theory. In collecting the data, there are several steps were performed. First, opening YouTube website and searching for the Melaney Ricardo YouTube channel. Second, downloading some videos of Melaney Ricardo YouTube channel which contain code-switching. Third, watching and listening the video repeatedly. Fourth, take note of the sentences in the video that involves code-switching. Fifth, determining the data based on the types of code-switching. The results of this study show that in Melaney Ricardoâ€™s video YouTube channel entitled Zacklee! â€œGue Jatoh Ke Dalam Dosa & Sempat Tidak Bisa Rasakan Tuhan Lagiâ€ there existed 51 occurrences of data which contain tag switching with 5 data or 9,8%, followed by Intra-sentential switching with 20 data or 39,2% data and Inter-sentential switching with 26 data or 51%. It was clear that the predominant type of code-switching used in this study was Inter-sentential switching. Meanwhile, tag switching was the lowest frequent type. Keywords: Code-Switching; Melaney Ricardo; YouTube